Applications of GIS and Remote Sensing for Biodiversity Mapping and Conservation a Case Study of Trichy District - Subramani, T; Pasupathy, P (International Journal of Engineering and Technology, 2018)
Utilization of GIS and remote detecting for biodiversity mapping is centers around the use of room borne remote detecting and GIS for biodiversity protection with regards to the best in class innovation which has improved the established approach. It surveys as of now accessible instruments, space-borne or satellite sensors giving information which can be utilized without examination or understanding for concentrate singular life forms, species arrays or natural networks on ground. Along these lines, the picture preparing and GIS procedures created to get data from the caught satellite information are checked on. In our undertaking looking into the utilization of remote detecting and GIS strategies for mapping, and modeling lichens and their territories.Â Â